SOCIAL DETERMINANTS OF MODERN MANAGEMENT MODELS TRANSFORMATION - O. B. Skorodumova (Научный вестник МГТУ ГА, 2016)
On the basis of the single out features of information society new needs for structures of social management are shown. Modern organizational models of management are described. The organizational structures corresponding to requirements of innovative management are revealed and characterized. The basic principles underlying the organization of management in forming a society of knowledge are revealed.